Assistive devices among people living at home with advanced cancer: Use, non‐use and who have unmet needs for assistive devices?. (14th March 2022) - Pilegaard, Marc Sampedro; la Cour, Karen; Baldursdóttir, Fjóla; Morgan, Deidre; Oestergaard, Lisa Gregersen; Brandt, Åse
Abstract: Objective: To investigate which assistive devices people with advanced cancer have and whether they are in use. In addition, to explore the characteristics of people with advanced cancer who have unmet needs for assistive devices. Methods: This descriptive cross‐sectional study used data from a randomised controlled trial evaluating efficacy of an occupational therapy‐based intervention. Participants were 237 people with advanced cancer. Data were collected by means of instruments about demography, functioning and assistive devices. Results: The most frequent assistive devices possessed by the participants were as follows: (1) small aids for dressing (47%), (2) Pillow for positioning (40%) and (3) electrically operated adjustable bed (39%). The prevalence of assistive devices was 92% (95% confidence interval [CI]: 88%–95%) with 14.2% non‐use, largest for trolley tables (50%). In all, 27.4% of the participants were found to have unmet needs for assistive devices. These participants had similar characteristics to the other participants except from lower activity of daily living (ADL) ability ( p values = <0.001). Conclusion: The assistive devices possessed by the participants were primarily for positioning and resting, and most were in use. More than a fourth of the participants had unmet needs for assistive devices and were characterised by lower ADL ability.